PERBEDAAN BAHASA INDONESIA STANDAR DENGAN BAHASA MELAYU SAMBAS : DI BIDANG FONOLOGI DAN KOSAKATA - Wisnu Arie Prasetyo; Umi Hartati (CARAKA, 2018)
This study aims to (1) describe the phonological differences of Standard Indonesian with Sambas Malay language and (2) to describe the differences of Indonesian Standard vocabulary with Sambas Malay. This type of research is a qualitative research that focuses on the designation of meaning, description, clarity, data placement in context. The data of this research are 200 basic vocabulary of Sambas language of West Kalimantan based on Swadesh List which is translated in Indonesian language. Data collection using the method refer, see libat ably, and record technique and recording techniques. The data analysis used in this research is the method of translational and articulatory phonetic, and using the law of appeal technique. The method of presentation of the results of this study was conducted by informal methods. The results of this study are (1) Differences in Indonesian phonology Standards with Sambas Malay Language (a) Corresponding differences include [a] - [e], [Ã˜] - [k], [n] - [Å‹], [h] - [k], [r] - [k], [t] - [k]. (b) irregular differences include [b] - [g], [o] - [u], [l] - [k]. (2) Differences in Indonesian vocabulary Standard with Sambas Malay language there are 18 vocabulary differences.